La recuperación del patrimonio del área metropolitana de Lima (Perú) a través del desarrollo turístico - Feliu Franch, Joan (PASOS Revista de Turismo y Patrimonio Cultural, 2006)
This article regarding the city and metropolitan area of Lima avoids sectorial or strictly macroeconomic focus. It offers a view on tourist development, considering its possibilities as an element of conservation of patrimony and its sustainability. The main objective is to improve the procedures and results by adapting succeeding models in order to achieve a concrete but also dynamic system